Coverage and quality radio analysis for single radio access network technology in GSM / Khairul Rahim Khairudin - Khairudin, Khairul Rahim
Single RAN is the Radio equipment which consists of Base Band Unit (BBU) and main processor for enabling GSM, UMTS and LTE in the same platform. In the past of 5 years, operators in Malaysia using separate radio equipment for different technologies. This caused big impact on the CAPEX and OPEX to the operators to manage and maintain their network. By having single RAN, operators automatically reduce their CAPEX and OPEX for every year to manage and maintain the radio equipment. The performance of the single RAN was studied in terms of coverage and quality compared to conventional radio.